A potential pyrrhotite (Fe7S8) anode material for lithium storage. Issue 19 (30th January 2015) - Zhang, Kailong; Zhang, Tingwei; Liang, Jianwen; Zhu, Yongchun; Lin, Ning; Qian, Yitai
Abstract : A new kind of electrode material for lithium ion batteries was prepared by a one-step solid–solid reaction. The structure, morphology and electrochemical properties of the Fe7 S8 @C nanospheres were investigated. Abstract : Fe7 S8 @C nanospheres were prepared by a simple solid–solid reaction and showed a high specific capacity and an excellent high rate performance as the anode material in lithium ion batteries. The core–shell Fe7 S8 @C composites delivered a very high reversible capacity of 695 mA h g −1 at 0.1 A g −1 after 50 cycles between 0.01 and 3.00 V. The Fe7 S8 @C composites also showed a discharge plateau at 1.5 V, cycling between 1.20 and 2.50 V, and exhibited a specific capacity of 397 mA h g −1 at 0.1 A g −1 over 200 cycles, which is higher than the theoretical capacity of Li4 Ti5 O12 (about 175 mA h g −1 ).